Pengaruh Permainan Gobak Sodor dan Bola Beracun Terhadap Minat Siswa dalam Pembelajaran PJOK di SMPN 3 Kalibening - Nur Zaini Akrom Sofwan; Bertika Kusuma Prastiwi; Agus Wiyanto (Universitas Hamzanwadi, 2026)
This study was motivated by the low interest of students in Physical Education, Sports, and Health (PJOK) learning due to monotonous teaching methods. This study aims to analyze the effect of traditional games of gobak sodor and poison ball on increasing students' interest in learning PJOK. The research used a quantitative approach with a non-equivalent group pretest-posttest quasi-experimental design. The sample consisted of two eighth-grade classes at SMPN 3 Kalibening who were given treatment through both games. Data were collected using a four-point Likert scale questionnaire that had been tested for validity and reliability. Data analysis was performed using the Wilcoxon Signed-Rank Test because some of the data were not normally distributed. The results showed a significant increase in student interest (Z = -5.352; p = 0.000), with an average score increase from 82.35 to 89.72. The Mann-Whitney U Test results showed no significant difference between the effects of the two games (p = 0.537). The discussion relates the findings to Self-Determination Theory, in which traditional games fulfill the psychological needs of autonomy, competence, and social connectedness, thereby increasing intrinsic motivation and interest in learning. The conclusion of the study confirms that the implementation of traditional games is effective in increasing student interest in PJOK, with the note that inclusive adaptation to student characteristics is necessary to maximize its impact.